Diffusion‐weighted double‐echo steady‐state with a three‐dimensional cones trajectory for non‐contrast‐enhanced breast MRI. Issue 5 (31st December 2020) - Moran, Catherine J.; Cheng, Joseph Y.; Sandino, Christopher M.; Carl, Michael; Alley, Marcus T.; Rosenberg, Jarrett; Daniel, Bruce L.; Pittman, Sarah M.; Rosen, Eric L.; Hargreaves, Brian A.
Abstract: The image quality limitations of echo‐planar diffusion‐weighted imaging (DWI) are an obstacle to its widespread adoption in the breast. Steady‐state DWI is an alternative DWI method with more robust image quality but its contrast for imaging breast cancer is not well‐understood. The aim of this study was to develop and evaluate diffusion‐weighted double‐echo steady‐state imaging with a three‐dimensional cones trajectory (DW‐DESS‐Cones) as an alternative to conventional DWI for non‐contrast‐enhanced MRI in the breast. This prospective study included 28 women undergoing clinically indicated breast MRI and six asymptomatic volunteers. In vivo studies were performed at 3 T and included DW‐DESS‐Cones, DW‐DESS‐Cartesian, DWI, and CE‐MRI acquisitions. Phantom experiments (diffusion phantom, High Precision Devices) and simulations were performed to establish framework for contrast of DW‐DESS‐Cones in comparison to DWI in the breast. Motion artifacts of DW‐DESS‐Cones were measured with artifact‐to‐noise ratio in volunteers and patients. Lesion‐to‐fibroglandular tissue signal ratios were measured, lesions were categorized as hyperintense or hypointense, and an image quality observer study was performed in DW‐DESS‐Cones and DWI in patients. Effect of DW‐DESS‐Cones method on motion artifacts was tested by mixed‐effects generalized linear model. Effect of DW‐DESS‐Cones on signal in phantom was tested by quadratic regression. Correlation was calculated between DW‐DESS‐Cones and DWI lesion‐to‐fibroglandular tissue signal ratios. Inter‐observer agreement was assessed with Gwet's AC. Simulations predicted hyperintensity of lesions with DW‐DESS‐Cones but at a 3% to 67% lower degree than with DWI. Motion artifacts were reduced with DW‐DESS‐Cones versus DW‐DESS‐Cartesian ( p  < 0.05). Lesion‐to‐fibroglandular tissue signal ratios were not correlated between DW‐DESS‐Cones and DWI ( r = 0.25, p = 0.38). Concordant hyperintensity/hypointensity was observed between DW‐DESS‐Cones and DWI in 11/14 lesions. DW‐DESS‐Cones improved sharpness, distortion, and overall image quality versus DWI. DW‐DESS‐Cones may be able to eliminate motion artifacts in the breast allowing for investigation of higher degrees of steady‐state diffusion weighting. Malignant breast lesions in DW‐DESS‐Cones demonstrated hyperintensity with respect to surrounding tissue without an injection of contrast. Level of Evidence: 2. Technical Efficacy Stage: 1.